Perancangan Dan Implementasi Game Edukasi Matematika Bahasan Trigonometri Berbasis Mobile (Studi Kasus SMK Pakuan Lembang) - Dahlan Dahlan; Tedi Mulyadi (Journal of Informatics and Electronics Engineering, 2022)
The level of mathematical ability of students in Indonesia based on the survey results of the Organization for Economic Co-operation and Development is still low. Various factors that affect the low ability of mathematics to learn are stress experienced by students who think that mathematics is difficult to understand, learning methods that affect the knowledge transfer process are not optimal. The use of technology in the learning process in visual form is one of several solutions to create an effective learning process. The type of visual form of learning media is in the form of games. This study aims to provide alternative learning about trigonometry based on mobile game mathematics in a case study at SMK Pakuan Lembang. Multimedia Development Life Cycle (MDLC). Applications were tested using the black box method (application test) and User Acceptend Test (UAT). The test results of 26 respondents on 3 variables (design, features and user satisfaction) showed that overall it was in accordance with user needs (85.4%).